Energy transfer between wind waves and low‐frequency oscillations on a fringing reef, Ipan, Guam. Issue 10 (9th October 2014) - Péquignet, Anne‐Christine N.; Becker, Janet M.; Merrifield, Mark A.
Abstract Field observations from a Guam fringing reef are used to examine the cross‐reef energy exchange between high‐frequency sea and swell (SS) and low‐frequency infragravity (IG) and far infragravity (fIG) waves. Energetic SS waves (significant wave heights 2–4 m) break at the outer reef, leading to weak (<1 m) conditions on the shallow reef flat. As SS waves shoal on the reef face before breaking, IG and fIG energy fluxes both increase through nonlinear energy transfer from the SS waves. In contrast, through the surf zone, the IG energy flux decreases whereas fIG flux increases. The decrease in IG energy flux through the surf zone is attributed to breaking SS waves working against the incident bound IG wave energy, which dominates breakpoint forced IG waves, yielding a net flux decrease. In contrast, fIG energy flux increases through the surf zone, consistent with breakpoint forcing and the absence of an energetic bound fIG component on the reef face. IG and fIG energy fluxes decay on the shallow reef flat due primarily to frictional dissipation, with tidal modulations attributed to nonlinear conversion and friction. Forcing at fIG frequencies may lead to a normal mode response on the reef with comparable incoming and outgoing fIG energy fluxes at the outer reef flat, depending on water level over the reef flat and the degree of frictional dissipation.